2018
DOI: 10.21273/hortsci13182-18
|View full text |Cite
|
Sign up to set email alerts
|

Using Market Segmentation Analysis to Identify Consumer Preferences for Fresh Peach Attributes

Abstract: Consumer preferences for attributes of fresh peach fruit in the United States are largely unknown on a national basis. We used a choice experiment to explore market segmentation based on consumer heterogeneous preference for fruit attributes including external color, blemish, firmness, sweetness, flavor, and price. We collected the data using an online survey with 800 U.S. consumers. Using a latent class logit model, we identified three segments of consumers differing by different sets of preferred qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…Willingness to pay was elicited from supply chain members for numerous quality traits of four rosaceous fresh market fruit crops 19 – 21 , with crop-specific investigations of apple 22 , 23 , peach 24 , 25 , sweet and sour cherry 26 , and strawberry 27 . Across crops, results indicated consumers were willing to pay a price premium for flavor and textural components over fruit appearance attributes like size and external/internal color.…”
Section: Genomics and Socio-economics Knowledge Informs All Stages Ofmentioning
confidence: 99%
“…Willingness to pay was elicited from supply chain members for numerous quality traits of four rosaceous fresh market fruit crops 19 – 21 , with crop-specific investigations of apple 22 , 23 , peach 24 , 25 , sweet and sour cherry 26 , and strawberry 27 . Across crops, results indicated consumers were willing to pay a price premium for flavor and textural components over fruit appearance attributes like size and external/internal color.…”
Section: Genomics and Socio-economics Knowledge Informs All Stages Ofmentioning
confidence: 99%
“…This is because the WTP for each attribute is conditional on the presence of the other attributes (Viegas et al ., 2014). This form of study has been widely conducted in other fresh fruits such as peach (Zhou et al ., 2018), apple, cherry (Gallardo et al ., 2018) and strawberry (Gallardo et al ., 2015; Choi et al ., 2017).…”
Section: Future Directionsmentioning
confidence: 99%
“…From the consumer perspective of fruit quality attributes, a number of studies have concluded that flavor, texture, firmness, larger size, and color are important determinants of consumer preferences (Campbell et al, 2013;Delgado et al, 2013;Olmstead et al, 2015). Zhou et al (2018) identified three market segments of U.S. peach consumers based on their preferences for key attributes: external fruit color, external appearance, size, firmness, sweetness, flavor, and price. The experienced attributeoriented market segment (49% of the sample of respondents) valued fruit taste and texture, the search attributeoriented market segment (34% of the sample) valued fruit appearance, and the balanced market segment (18% of the sample) valued both fruit quality and appearance.…”
Section: Literature Reviewmentioning
confidence: 99%